2010
DOI: 10.1007/s10535-010-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid pretreatment on cadmium toxicity in wheat

Abstract: Cadmium (100, 400 and 1000 µM CdCl 2 ) treatments resulted in the inhibition of root dry biomass, root elongation and increased Cd accumulation in wheat (Triticum aestivum L.) roots. Further, these treatments decreased relative water content, chlorophyll content, 14 CO 2 -fixation, activities of phosphoenolpyruvate carboxylase and ribulose-1,5-bisphosphate carboxylase and abscisic acid content while increased malondialdehyde, hydrogen peroxide and free proline contents. Chloroplast and root ultrastructure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 44 publications
7
34
0
Order By: Relevance
“…1e, f). This finding is in agreement with the observations of Moussa and El-Gamal (2010) in wheat. The improvement in chloroplast structure might provide the primary explanation for the increase in the photosynthesis rate after SA pretreatment and the absence of a significant effect on Gs and E compared with 500 lM Cd treatment (Table 2).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1e, f). This finding is in agreement with the observations of Moussa and El-Gamal (2010) in wheat. The improvement in chloroplast structure might provide the primary explanation for the increase in the photosynthesis rate after SA pretreatment and the absence of a significant effect on Gs and E compared with 500 lM Cd treatment (Table 2).…”
Section: Resultssupporting
confidence: 94%
“…In plant cells, the vacuoles are involved in the sequestration of Cd and, consequently, in Cd-induced tolerance (Sanitá di Toppi and Gabbrielli 1999). The occurrence of electron-dense deposits in the vacuoles and appearance of small vesicles in the cytoplasm appeared to be common features of metal-stressed plants and suggested a mechanism of heavy metal detoxification in plants (Moussa and El-Gamal 2010). Our study confirmed that the root tip cells of I. hexagona seedlings possessed small vacuoles with high electron density granules.…”
Section: Resultssupporting
confidence: 79%
“…In fact, Cd has remarkable effect reducing the growth of non-tolerant plants (Benavides et al, 2005;Gratão et al, 2005). In addition, this metal can constrain the root biomass allocation (Moussa and El-Gamal, 2010) as well as the leaf elongation and shoot biomass (Ye et al, 1997). Hadad et al (2010) reported that Typha domingensis showed no growth modification under the contamination of Cr, Ni and Zn.…”
Section: Discussionmentioning
confidence: 99%
“…SA plays an important role in plant disease resistance (Klessig and Malamy 1994;Popova et al 1997) and now widely accepted as a major signal transducer or messenger for biotic stress (Klessig and Malamy 1994;Ganesan and Thomas 2001). More recent studies reported that the externally applied SA increased plant's tolerance to several abiotic stresses, including osmotic stress (Singh and Usha 2003;Al-Hakimi 2006), drought (Azooz and Youssef 2010), salinity (Shakirova et al 2003;Gunes et al 2007), and heavy metal stress Moussa and El-Gamel 2010). These studies suggest that SA may enhance the multiple types of stress tolerance in plants through which interactive effects on several functional molecules or other signaling molecules participating in more complex stress responses.…”
Section: Introductionmentioning
confidence: 99%